Tracking Infection and Genetic Divergence of Methicillin-Resistant Staphylococcus aureus at Pets, Pet Owners, and Environment Interface - Shoaib, Muhammad; Aqib, Amjad Islam; Ali, Muhammad Muddassir; Ijaz, Muhammad; Sattar, Huma; Ghaffar, Awais; Sajid Hasni, Muhammad; Bhutta, Zeeshan Ahmad; Ashfaq, Khurram; Kulyar, Muhammad Fakhar-e-Alam; Pu, Wanxia (Frontiers in Veterinary Science, 2022)
Staphylococcus aureus (S. aureus) has become leading animal as well as public health pathogen that keeps on transferring from one host to other giving rise to newer strains by genetic shifts. The current study was designed to investigate the epidemiology and genetic relatedness of mecA gene in S. aureus isolated from pets, immediate individuals in contact with pets and veterinary clinics environment. A total of n = 300 samples were collected from different veterinary hospitals in Pakistan using the convenient sampling technique. The collected samples were subjected to microbiological and biochemical examination for isolation of S. aureus. Methicillin resistance was investigated by both phenotypically using oxacillin disk diffusion assay and genotypically by targeting mecA gene by PCR. PCR amplicons were subjected for sequencing by Sanger method of sequencing which were subsequently submitted to NCBI GenBank under the accession numbers MT874770, MT874771, and MT874772. Sequence evolutionary analysis and mecA gene characterization was done using various bioinformatics tools. Overall, 33.66% mecA gene harboring S. aureus strains was isolated from all sources which was separately noted as 33.33% from pets, 46.0% from surrounding and 28.0% from immediate contact individuals. The bioinformatics analysis noted that one SNP was identified at position c.253C>A (Transvertion). Phylogenetic tree (two clades) of S. aureus mecA revealed possibility of inter-transmission of disease to and from environment and pets. Frequency of adenine and thymine nucleotide in motifs were found same (0.334) while cytosine and guanine frequency were same (0.166). Threonine was replaced by asparagine (p. T84D) in one each sample from cat, environment and human source. On the other hand, protein structure of cat-1 and cat-2 proteins was found identical while cat-3, environmental and human proteins shared identical structures. The study thus concludes rising circulation of MRSA strains at animal-human-environment interface forecasting development of novel strains with modified range of resistance.